The effectiveness of Personal Computers (PC) preventive maintenance services by DiGiCiTY (M) Sdn Bhd on government agencies in the state of Malacca - Azmi, Mohd Dzulkarnaen (2002)
A research entitled "The Effectiveness of Personal Computer (PC) Preventive Maintenance Services By DiGiCiTY (M) Sdn Bhd on Government Agencies in The States of Malacca". The objective of this research is to determine the effectiveness preventive maintenance services as a single method in maintaining the computer performance and the results matches the expectation of customers, also the quality in delivering the services by DiGiCiTY staffs. The researcher had focused the study at DiGiCiTY (M) Sdn Bhd located at DiGiCiTY (M) SDN BHD 16 & 16A, Jalan Cempaka 1 Taman Sri Cempaka, 75400 Pringgit, Melaka, The researcher had used questionnaire distribution to gather information from the staff for the topic chooses by the researcher. 40 questionnaire have been distributed to respondents in 40 government agencies which uses the MIMOS personal computers. DiGiCiTY (M) Sdn Bhd uses preventive maintenance system in order to keep up with the latest technology and avoid problem before it occurred. Either hardware or software part of the Persona! Computer, it needs a good maintenace system in upgrading the performance according to the tasks and work that need to be done. Good maintenance services can guaranteed satisfaction and good working performance. Preventive maintenance has a lot of advantages like it saves time, money and safeguard the important data. The key to a successful Preventive Maintenance program is scheduling and execution. Priority should be given to preventive maintenance and a very aggressive program to monitor the schedule and ensure that the work is completed according to schedule should be in place. This study also shows the quality of DiGiCITY (M) Sdn Bhd staff in delivering the preventive maintenance service to the customer. Besides me services itself, technician knowledge and skill while performing the services also can effected the results.